1983
DOI: 10.1136/jmg.20.4.280
|View full text |Cite
|
Sign up to set email alerts
|

The fragile X: a scanning electron microscope study.

Abstract: SUMMARY Scanning electron microscopy (SEM) has been used to study the fragile X chromosome.The fragile site appears as an isochromatid gap in the majority of cases, confirming light microscope (LM) observations. SEM has allowed a more precise location of the fragile site to the Xq27-3 region.Light microscope (LM) studies have indicated that the fragile site on the X chromosome is most frequently observed as a non-staining gap of variable width, usually involving both chromatids. However, there is some uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(26 citation statements)
references
References 7 publications
2
24
0
Order By: Relevance
“…The images of AFM are compatible with previous scanning electron microscopy studies (Harrison et al 1983).…”
Section: Introductionsupporting
confidence: 76%
“…The images of AFM are compatible with previous scanning electron microscopy studies (Harrison et al 1983).…”
Section: Introductionsupporting
confidence: 76%
“…The precise location of the X-linked fragile site has now been established by prophase banding (22) and by electron microscopy (23) to be Xq27.3. Formal genetic analysis (Table 1) had previously shown close linkage of G6PD to hemophilia A (25), Deutan and Protan color blindness (12,28), and adrenal leukodystrophy (27).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lubs reported that the affected males had macroorchidism (large testes); large, low-set ears; asymmetric facial features, and large hands (Lubs 1969;von Reyn et al 1978). After mapping of this chromosomal variation to Xq27.3 (Harrison et al 1983) and confirming the fragile site in many families segregating ID, the disorder became known as fragile X syndrome (FXS). Affected males have moderate to severe ID,speechdelay,andmotorabnormalities.Common psychiatric features include hyperactivity, anxiety, and severe autism spectrum phenotypes.…”
Section: Clinical Features and Phenotypic Spectrummentioning
confidence: 99%